2015
DOI: 10.1002/adma.201503661
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Self‐Healing Diselenide‐Containing Polyurethane Elastomer

Abstract: Visible light is an easily achievable and mild trigger for self-healing materials. By incorporating dynamic diselenide bonds into polyurethane, visible-light-induced self-healing materials can be fabricated. Besides mild visible light, the healing process can also be realized using directional laser irradiation, which makes the system a remotely controllable self-healing system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
237
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(253 citation statements)
references
References 64 publications
4
237
0
1
Order By: Relevance
“…At least, laser-induced nanocapsule disintegration and transformation may be exploited for the contactless remote-controlled transformation of LM and replace traditional contact-dependent electrical stimulation6 or the passive oxidation-reduction treatment of cells10. In addition, this light-promoted disintegration and transformation of LMs would be useful for laser welding technology48, targeted connecting for the transected nerves1631 and electronics49 and non-contact wiring on electrodes of flexible diagnostic devices50 by a highly focused continuous wave (CW) laser beam with low power. We also consider that rapid morphological changings of laser-driven LM nanocapsules is promising for active drug delivery system in comparison to the slow and passive transformable properties410 of previous reported LM nanocomplexes under an acidic condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least, laser-induced nanocapsule disintegration and transformation may be exploited for the contactless remote-controlled transformation of LM and replace traditional contact-dependent electrical stimulation6 or the passive oxidation-reduction treatment of cells10. In addition, this light-promoted disintegration and transformation of LMs would be useful for laser welding technology48, targeted connecting for the transected nerves1631 and electronics49 and non-contact wiring on electrodes of flexible diagnostic devices50 by a highly focused continuous wave (CW) laser beam with low power. We also consider that rapid morphological changings of laser-driven LM nanocapsules is promising for active drug delivery system in comparison to the slow and passive transformable properties410 of previous reported LM nanocomplexes under an acidic condition.…”
Section: Resultsmentioning
confidence: 99%
“…This knowledge could be, especially, very useful for the development of nanoscale stimulators, such as power sources for deep brain stimulation and optical biotelemetry, and the creation of unique cell therapies and tissue engineering. Finally, we believe the dramatic morphological changes to LM triggered by NIR irradiation could also be used for light-induced wiring on electrical devices4849 and light-driven self-healing materials50 in addition to the improvement of biomedical theranostic effects for various disease treatment and care.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, efforts were made to achieve autonomic healing free of manual intervention under visible light. Polymers containing reversible thiuram disulfide 19 and diselenide 20 bonds proved to be self-healable with tabletop lamp.…”
Section: Introductionmentioning
confidence: 99%
“…[223,224] Extensive work has been done to demonstrate self-healing dielectric material [225] and gels, [226,227] however it is challenging to fabricate a self-healing current collector for the realization of a completely self-healing transparent and stretchable electronic device. It is extremely difficult to achieve selfhealing ability with electronic conductors.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Meanwhile, the ionic conductor can be easily tuned to repair itself while sustaining its transparency, stretchability, and ionic conductivity. One way to realize a self-healing ionic conductor is by using a polymer matrix comprised of bonds that are stable and reversible such as dynamic covalent bonds [223,224] and hydrogen bonds. [231,232] Cao et al reported highly self-healing STIC using ion-dipole interactions.…”
Section: Challenges and Outlookmentioning
confidence: 99%